2016
DOI: 10.1038/srep34479
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical phosphorylation of apical membrane antigen 1 is required for efficient red blood cell invasion by malaria parasites

Abstract: Central to the pathogenesis of malaria is the proliferation of Plasmodium falciparum parasites within human erythrocytes. Parasites invade erythrocytes via a coordinated sequence of receptor-ligand interactions between the parasite and host cell. One key ligand, Apical Membrane Antigen 1 (AMA1), is a leading blood-stage vaccine and previous work indicates that phosphorylation of its cytoplasmic domain (CPD) is important to its function during invasion. Here we investigate the significance of each of the six av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(68 citation statements)
references
References 52 publications
1
67
0
Order By: Relevance
“…Substitution of AMA1 Ser 610 with an alanine using a conditional transgenic approach led to a dramatic reduction in merozoite invasion [ 54 ]. A later report confirmed the PKA-dependent phosphorylation of AMA Ser 610 , and showed that phosphorylation of Ser 610 is an initial step that is needed before subsequent phosphorylation of Thr 613 by the parasite glycogen synthase kinase 3 (GSK3; PF3D7_0312400) required for efficient invasion [ 103 ]. As mentioned above, a regulatory role for cAMP and PfACβ in calcium release and microneme secretion has been demonstrated using a low K + buffer system [ 5 ].…”
Section: A Role For Pka In Multiple Life-cycle Stages Is Emergingmentioning
confidence: 99%
“…Substitution of AMA1 Ser 610 with an alanine using a conditional transgenic approach led to a dramatic reduction in merozoite invasion [ 54 ]. A later report confirmed the PKA-dependent phosphorylation of AMA Ser 610 , and showed that phosphorylation of Ser 610 is an initial step that is needed before subsequent phosphorylation of Thr 613 by the parasite glycogen synthase kinase 3 (GSK3; PF3D7_0312400) required for efficient invasion [ 103 ]. As mentioned above, a regulatory role for cAMP and PfACβ in calcium release and microneme secretion has been demonstrated using a low K + buffer system [ 5 ].…”
Section: A Role For Pka In Multiple Life-cycle Stages Is Emergingmentioning
confidence: 99%
“…A role for cyclic GMP (cGMP)–dependent protein kinase (PKG) has been demonstrated in blood stage egress [1, 2] and invasion [3], gametogenesis [4], ookinete motility [5, 6], and sporozoite motility required for invasion of mosquito vector salivary glands and host hepatocytes [79]. Available evidence suggests a role for cyclic AMP (cAMP)–dependent protein kinase (PKA) in blood stage invasion [1012], cell cycle progression [13, 14], anion conductance, and gametocyte deformability [15, 16] as well as regulated exocytosis of sporozoite apical organelles and hepatocyte infectivity [17]. Two recent studies on cAMP signalling in Toxoplasma gondii have shown that absence of one of the three PKA catalytic subunits (PKAc1) leads to premature egress of tachyzoites [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…When EBA175 function is ablated (e.g., genetically), some strains are able to switch to an alternative invasion pathway using the interaction of Rh4 and its receptor CR1 (12). The precise function of each ligand-receptor complex during invasion is largely unknown; however, in recent years, it has become clearer that these interactions do not merely serve for adhesion but, instead, may be involved in transducing signals into either the merozoite (13,14) or potentially the RBC (7).Recently, we attempted to model invasion in terms of the biophysical forces required to enwrap a merozoite toward full RBC entry. Of particular focus were the properties of membrane tension (which, in the RBC, is primarily provided by the cytoskeleton) and bending modulus (the energy required to cause bending of the lipid bilayer) (15).…”
mentioning
confidence: 99%
“…When EBA175 function is ablated (e.g., genetically), some strains are able to switch to an alternative invasion pathway using the interaction of Rh4 and its receptor CR1 (12). The precise function of each ligand-receptor complex during invasion is largely unknown; however, in recent years, it has become clearer that these interactions do not merely serve for adhesion but, instead, may be involved in transducing signals into either the merozoite (13,14) or potentially the RBC (7).…”
mentioning
confidence: 99%